Extent of East-African Nurse Leaders’ Participation in Health Policy Development - N. Shariff; E. Potgieter (Nursing Research and Practice)
This paper reports part of a bigger study whose aim was to develop an empowerment model that could be used to enhance nurse leaders’ participation in health policy development. A Delphi survey was applied which included the following criteria: expert panelists, iterative rounds, statistical analysis, and consensus building. The expert panelists were purposively selected and included national nurse leaders in leadership positions at the nursing professional associations, nursing regulatory bodies, ministries of health, and universities in East Africa. The study was conducted in three iterative rounds. The results reported here were gathered as part of the first round of the study and that examined the extent of nurse leaders’ participation in health policy development. Seventy-eight (78) expert panelists were invited to participate in the study, and the response rate was 47%. Data collection was done with the use of a self-report questionnaire. Data analysis was done by use of SPSS and descriptive statistics were examined. The findings indicated that nurse leaders participate in health policy development though participation is limited and not consistent across all the stages of health policy development. The recommendations from the findings are that health policy development process needs to be pluralistic and inclusive of all nurse leaders practicing in positions related to policy development and the process must be open to their ideas and suggestions.